ANALISIS TEKS ARGUMENTASI SISWA SEKOLAH MENENGAH DALAM PEMBELAJARAN MEMBACA PUISI - Sari, Wulan Puspita; Firmansyah, Dida (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Literature is a paper that is made with many ways of imagination, especially in terms of appreciating the quite complex style and manner that is varied by the appreciator. The researcher tried to apply literary appreciation techniques which especially appreciated poetry by analyzing the text of the arguments contained in poetry. The researcher formulated several problems that might occur during the research process, namely how the results of the text argumentation in learning to read poetic texts. The method used is a descriptive method that allows a broader description of the object being analyzed. The results of the analysis obtained are about the elements that make up poetry, style and the style of language used, diction and meaning implied in the content of the poem. The researcher expects a lot of benefits from the analysis of the poem which at least adds insight into poetry, analysis of poetry and appreciation in different ways and points of view.